GLOBAL DIETARY TRENDS: ANALYZING PROTEIN CONSUMPTION PATTERNS IN SHANGHAI AND AMSTERDAM - Janssen , Helena (Ayden Journal of Agriculture and Allied Studies, 2024)
Developing countries are witnessing a nutritional and economic transformation marked by a shift from plant-based protein to animal-based protein consumption. This transition, driven primarily by rising incomes, carries significant environmental and sustainability implications. While it is widely recognized that the growing consumption of animal-based protein is unsustainable and detrimental to natural ecosystems, climate stability, and resource usage, the choice of animal protein source is influenced by a complex interplay of factors including governmental policies, cultural norms, and religious beliefs. This paper delves into the challenges posed by the increasing production and consumption of animal-based proteins, emphasizing their adverse environmental impact. The production of animal proteins demands more resources, such as freshwater and energy, per gram compared to plant-based proteins. Moreover, it results in higher greenhouse gas emissions, exacerbating global warming and climate change concerns. In contrast, developed countries are now promoting a reverse protein transition: a shift from animal proteins to plant proteins. This paper sheds light on this emerging trend, highlighting its potential to mitigate the environmental consequences associated with protein production and consumption.